2016
DOI: 10.3390/ijms18010009
|View full text |Cite
|
Sign up to set email alerts
|

Plant MicroRNAs—Novel Players in Natural Medicine?

Abstract: MicroRNAs (miRNAs) represent a class of small non-coding RNAs that act as efficient gene expression regulators and thus play many important roles in living organisms. Due to their involvement in several known human pathological and pathogenic states, miRNA molecules have become an important issue in medicine and gained the attention of scientists from the pharmaceutical industry. In recent few years, a growing number of studies have provided evidence that miRNAs may be transferred from one species to another a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 132 publications
1
58
0
Order By: Relevance
“…In particular, rice miR168a has been suggested to target the mRNA of the low-density lipoprotein receptor adaptor protein 1, and rice-fed mice showed a reduction in receptor expression in blood and liver. Evidences also indicated that the integration of exogenous miR168 from plants can contribute to modulate dyslipidemia in mammals [64,68]. The presence of rice miRNAs in human plasma was further supported by Wang, who using next generation small RNA sequencing datasets of human serum samples, identified several exogenous small RNA species from gut microbiota and plant species [69].…”
Section: Mirnas and Evolutionmentioning
confidence: 88%
“…In particular, rice miR168a has been suggested to target the mRNA of the low-density lipoprotein receptor adaptor protein 1, and rice-fed mice showed a reduction in receptor expression in blood and liver. Evidences also indicated that the integration of exogenous miR168 from plants can contribute to modulate dyslipidemia in mammals [64,68]. The presence of rice miRNAs in human plasma was further supported by Wang, who using next generation small RNA sequencing datasets of human serum samples, identified several exogenous small RNA species from gut microbiota and plant species [69].…”
Section: Mirnas and Evolutionmentioning
confidence: 88%
“…There are a number of recent advances in approaches using miRNAs for cancer treatment, 53,54 including early efforts at developing edible plants that express miRNAs for treatment of human diseases. 55 In this context, approaches that reconstitute MIR143-3p could have an impact on the prevention and or treatment of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Following the discovery of cross-kingdom regulation mediated by plant miRNAs in mammalian tissues and cells [3,33], an increasing body of literature has shown that exogenous miRNAs derived from various species, including plants and viruses, play a critical role in modulating mammalian cell function [34][35][36]. Although these exogenous miRNAs execute their biological function in the recipient cells mainly through base-pairing the transcript of target genes in a manner of endogenous miRNA [34,35], certain exogenous miRNAs that contain the TLR-binding GU-rich motif can also directly bind to intracellular TLRs or cell surfaces, leading to activation of TLR-mediated immune responses.…”
Section: Direct Binding To Immune Cell Tlrs By Non-coding Small Rnasmentioning
confidence: 99%